Religious personality and gender differences in the perceived behaviour towards inter-ethnic everyday life among youths - Idris, Fazilah; Mastor, Khairul Anwar; Hamzah, Azimi; Tamam, Ezhar; Wong, Su Luan; Suradi, Nur Riza (Universiti Putra Malaysia Press, 2008)
The present study examined the influence of religious personality, as the manifestation of one’s religious belief, on the inter-ethnic perceived behaviour among the different ethnic and gender backgrounds. Religious personality comprises of three major factors: pro-social behaviour, ritual behaviour and anti-social behaviour. It was hypothesized that religious personality of the youth might influence inter-ethnic perceived behaviour by enhancing mutual understanding and respect, tolerance, and appropriate behaviour to live in peace and harmony. Respondents were 563 high school students, who were randomly selected from various schools in Selangor. The Inter-ethnic Tolerance Questionnaire (IETQ) was used as a self-designed questionnaire to measure the inter-ethnic perceived behaviour and the Universal Religious Personality Inventory (URPI) (Krauss et al., 2006). The findings gathered in the present study indicated that Indian, Malay and Chinese students scored the highest levels of the pro-social behaviour, ritual behaviour and anti-social behaviour, respectively. Comparing the genders among all races, female students were found to score higher than the male students in the pro-social behaviour, but scored lower in the anti-social behaviour. The multiple regression analysis indicated that the pro-social factor was found to be a significant positive predictor of the inter-ethnic perceived behaviour.